Sherlock Holmes' Last Case: A Reply to Ronen - Flamholtz, E.; Holmes, S. (Journal of Accounting Research, 1972)
Holmes' comment was addressed to Dr. Watson who had just expressed astonishment that Holmes was ignorant of the Copernican theory of the solar system. In truth, Holmes' reply to Watson expressed my exact sentiments after reading Ronen's review. Why? Because I found that I would have to answer the following question in the negative after almost every point he made: Would I do anything differently in view of what Ronen has stated?